Topará en Pisco: patrón de asentamiento y paisaje - Peters, Ann (2013)
The settlement pattern associated with the presence of the Topara ceramic tradition in the lower Pisco River watershed and ad-jacent coastal plain is analyzed based on fieldwork and mapping carried out between 1985 y 1987 and an update process asso-ciated with establishing geographic coordinates for the site of Chongos in 2013. Available data on Paracas tradition occupationsis compared with evidence for occupations and associated architecture in the Jahuay and Chongos phases, as well as Carmenoccupations, also associated with early Nasca. Site locations are related to the development and management of water-basedresources and communication routes, and to the processes of human modification of the landscape on the south central coast ofPeru. Re-analysis of mid-20th century aerial photographs and the fieldwork by Dwight Wallace is central to this study, alongwith amplification of the research topics and the physical areas he covered. Data on architectural patterns, evidence for associatedactivities, and artifact associations provide criteria for evaluating the relationship between the Pisco Valley occupations, those atthe Paracas site, and other contemporary occupations in the south coast region.